Observer-Based Aperiodic Time-Triggered Intermittent Control for Exponential Consensus of Multi-Agent Systems - Xueming Xu; Qingzhi Wang; Baozeng Fu; Lijie Wang (IEEE Access)
In this paper, an observer-based aperiodic time-triggered intermittent control protocol (OATICP) is explored for achieving exponential consensus of multi-agent systems (MASs). The mathematical expression of OATICP is initially put forward. OATICP only relies on the output information at sampling instants to estimate the state of the agent itself, and the state estimation information of the neighbor agents at sampling instants to generate the control signal. Then, for the exponential consensus of MASs under OATICP, the mixed Lyapunov functional (MLF) is constructed to establish sufficient conditions. Thirdly, by resorting to linear matrix inequality (LMI) and singular value decomposition (SVD) techniques, OATICP can be designed to realize the exponential consensus of MASs. As a result, a corollary is obtained. Finally, two simulation examples are provided for verification.